Guidelines for developing recommendations on changing ‘multimedia technologies’ course content according to data analysis of job regional open positions on hh.ru site - Levchenko, Natalia; Dzhaparova, Saltanat; Sedova, Nelly; Sedov, Victor; Bazhenov, Ruslan; Chuyko, Olga (AIP conference proceedings, 2022)
The paper is devoted to a series of studies aimed at processing the data on job searches in Vladivostok, published on the open specialized Internet site hh.ru, followed by the development of tips for improving ‘Multimedia Technologies’ training course. An open-source analytics platform Knime.com was used to review the data. The article deals with the findings of the analysis, which show a certain level of salaries for occupations that require professional skills in ‘Multimedia Technologies’ course content. The survey of the 1st -4th-year students of 09.03.01 IT and Computer Science major was carried out at Maritime State University named after Admiral G.I. Nevelskoy to test a hypothesis about the necessity of making adjustments in the subject syllabus. 74 people participated in the survey. Finally, practical hints for improving Multimedia Technology training course content are given to perfect the course to meet the needs of both students and potential employers.